Simulation as Support to evaluate UMP - da Silva, Marina Laisa; Pasin, Marcia (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: To provide continuous mobility, municipalities need to rethink the transport system in cities, described in the Urban Mobility Plan (UMP). Problem: Before proposing changes to UMP, it is necessary to evaluate the improvements in relation to the available infrastructure. This can be accomplished through computer simulation. Therefore, one of the major challenges to simulation is data lacking. Solution: This work evaluates changes to UMP and their impacts on urban mobility using different traffic flows, supported by computer simulation. Web information is used to generate lacking data. IS (Information System) Theory: Computer simulation can support the decision making process and allow municipalities evaluating different situations before making changes to the current traffic scenario. Method: Simulation of traffic scenarios using Web information to generate lacking data. The resulting output can support the decision making process. Summary of Results: According to the experiments carried out in the context of this work, considering different traffic scenarios, there was a drop of 4% in CO2, 15% in CO, 10% in HC, 4% in NOX, 5% in fuel consumption and 7% reduction in travel times. Contributions and Impact in the IS area: The main contribution of the article is to enable a technology based on traffic simulation for evaluation of UMP that can provide information and support for decision making process even with the absence of a full dataset.